Connecting at the intersection: Conversing identities on a street corner in Cape Town - Calleja, Remi (University of Cape Town, 2020)
The research proposes to unpack the process of identity negotiation among a group of Cape Bush doctors, as well as to reflect on my own negotiation. During the time spent together, these claimants of a KhoeSan identity presented a permeating Rastafari sense of belonging and reconnected with their Indigenous identity through their work with herbs. The research participants challenged hegemonic perspectives on identity, culture, health, and respectability. They carried out their practices and beliefs within an urban environment represented by the space of the street corner. A central relational ontology emerged throughout the research, emphasizing the multiple underlying connections and interdependencies that structure their worldview and deeply influencing my personal development. The negotiation of their identity was shaped by constant processes of re-appropriation, adaptation, and re-composition and contributed to bridging historical, cultural, and social gaps imposed by years of colonisation, oppression, and marginalisation. I argue in this research that understanding the production of identity through a dynamic and fluid framework of knowledge participates to foster reinterpretations of agency, power, wealth, and marginality. To contend with the plurality of crisis we face in the contemporary moment, We must learn from these alternative worldviews.